Insight into the role of facultative bacteria stimulated by micro-aeration in continuous bioreactors converting LCFA to methane - Duarte, Maria Salomé (2018)
Conversion of unsaturated long chain fatty acids (LCFA) to methane in continuous bioreactors is not fully understood. Palmitate (C16:0) often accumulates during oleate (C18:1) biodegradation in methanogenic bioreactors, and the reason why this happens and which microorganisms catalyze this reaction remains unknown. Facultative anaerobic bacteria are frequently found in continuous reactors operated at high LCFA loads, but their function is unclear. To get more insight on the role of these bacteria, LCFA conversion was studied under microaerophilic conditions. For that, we compared bioreactors treating oleate-based wastewater (organic loading rates of 1 and 3 kg COD m-3 d-1), operated under different redox conditions (strictly anaerobic-AnR, -350 mV; microaerophilic-MaR, -250 mV). At the higher load, palmitate accumulated 7 times more in the MaR, where facultative anaerobes were more abundant, and only the biomass from this reactor could recover the methanogenic activity after a transient inhibition. In a second experiment, the abundance of facultative anaerobic bacteria, particularly Pseudomonas spp. (from which two strains were isolated), was strongly correlated (p<0.05) with palmitate-to-total LCFA percentage in the biofilm formed in a continuous plug flow reactor fed with very high loads of oleate. This work strongly suggests that micro-aeration stimulates the development of facultative bacteria that are critical for achieving LCFA conversion to methane in continuous bioreactors. Microbial networks and interactions of facultative and strict anaerobes in microbial communities should be considered in future studies.